Examining consumer preferences for basic foodstuffs in a highly inflationary economic environment: The case of price-capped chicken breast fillet in Hungary - Zalán Márk Maró; Áron Török; Péter Czine (Heliyon)
In recent months, the European Union has experienced inflation that has not been seen for decades. Inflation and inflation expectations are crucial in economic and purchasing behaviour, as they influence consumption. Hungary had the highest inflation among the Member States of the European Union. To deal with this, the Hungarian government introduced price caps on certain basic foodstuffs. Chicken breast fillets are classified among these officially priced products, and based on per capita consumption in Hungary, poultry can be considered the most popular meat. The research aims to examine the preferences of Hungarian meat consumers regarding chicken breast fillets, considering their inflation expectations. Based on an online survey conducted in Hungary (n = 500), a latent profile analysis and an object case best-worst scaling approach were applied. Two-thirds of respondents are largely pessimistic about the future economic environment and the development of consumer prices. Best-Worst scores reveal that freshness, health impact and price are among the most significant considerations, while brand and place of origin are among the attributes considered least important. However, among the clusters distinguished based on inflation expectations, there are notable differences in assessing the importance of these attributes, which serve as the basis for managerial and policy implications.